(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study aims to analyze the effectiveness of public policies in promoting sustainable development in the government sector, with a focus on planning, implementation, and evaluation of policies that have an impact on economic, social, and environmental aspects. Sustainable development is an important concept in efforts to achieve a balance between economic growth, social justice, and environmental protection, which is a major challenge for governments in many countries, including Indonesia. Through a qualitative approach with a case study method, this study identifies various factors that influence the success or failure of public policies in achieving sustainable development goals. The results of the study indicate that factors such as public participation, stakeholder involvement, policy oversight, and synergy between the government, private sectors, and international institutions play a major role in determining the success of policies. In addition, the main challenges faced are the imbalance between planning and implementation, as well as resistance to change from some communities and certain sectors. As a recommendation, this study suggests that sustainable development policies be based on accurate data, improve transparent monitoring and evaluation systems, and strengthen cross-sectoral cooperation. With these steps, it is hoped that public policies can be more effective in promoting development that not only prioritizes economic growth, but also social justice and environmental protection for sustainability in the future.